Guided tissue regeneration and orthodontic movement for the treatment of pathological migration in esthetic zone - Vaishnavi Ramakant Chodankar; Nikita Ravindra Baheti; Vaibhav Anandrao Karemore; Wasundhara Ashok Bhad; Mangesh Bhalchandra Phadnaik; Santosh Jetu Chavan (Wolters Kluwer Medknow Publications, 2023)
Pathological migration is one of the chief complaints of patients-seeking dental treatment. It results in difficulty in mastication, speech, poor esthetic appearance, and decreased self-confidence. The prevalence ranges from 21.73% to 55.8% in patients having moderate-to-severe periodontitis. In this presentation, a 38-year-old adult male, systemically healthy, nonsmoking presented with the complaint of mobility and forward displacement of maxillary anterior tooth causing poor esthetic appearance and low self-esteem. He was treated with the interdisciplinary approach of periodontal and orthodontic intervention. Two-year posttreatment follow-up shows significant improvement in esthetics, periodontal status, and boosted the self-confidence of the patient and improved the oral health-related quality of life. This case emphasizes the importance of regenerative therapy and orthodontic movement for the treatment of periodontally compromised pathologically migrated tooth in adult patient.